Perencanaan Pengendalian Persediaan Bahan Baku dengan Metode Manufacturing Resource Planning - Sulaksmi, Andri (Department Industrial Engineering, University of Muhammadiyah Malang, 2008)
Planning material control have a purpose to compile a system capable to yield information to conduct correct action (reordering, scheduleng repeat, determining the amount of requirement at the time of is correct). One of the step performed within standard material control that is deermining best raw material ordering method utilize to get the expense of mot message of minimum. Utilize to support plan produce which have been made and fulfill Planned Order Release pursuant to calculation of MRP hence one of the capacities type from company that is labour factor had also have to be reckoned by do existing amount last for fulfilling requirement which have been reckoned. The object of this UD PATRIOT which located in Mojokerto.This company produce various shoes type which in its operation have constrain in determining best ordering method to each every ordered by raw material item as well as standart material control system which good to menimalize production cost. Planning material control by using this MRP II system was proposed to be applied by at company utilize to yield correct action that is determining maount, time, scheduling repeat, and ordering execution requirement of raw material. With applying MRP II can cost effective equal to Rp4,372,413.88 or 35.91% from expense of before using MRP II.